Labour Market Flows: Accounting for the Public Sector - Idriss Fontaine; Ismael Galvez-Iniesta; Pedro Maia Gomes; Diego Vila-Martin (Institute of Labor Economics (IZA), 2019)
For the period between 2003 and 2018, we document a number of facts about worker gross flows in France, the United Kingdom, Spain and the United States, focussing on the role of the public sector. Using the French, Spanish and UK Labour Force Survey and the US Current Population Survey data, we examine the size and cyclicality of the flows and transition probabilities between private and public employment, unemployment and inactivity. We examine the stocks and flows by gender, age and education. We decompose contributions of private and public job-finding and job-separation rates to fluctuations in the unemployment rate. Public-sector employment contributes 20 percent to fluctuations in the unemployment rate in the UK, 15 percent in France and 10 percent in Spain and the US. Private-sector workers would forgo 0.5 to 2.9 percent of their wage to have the same job security as public-sector workers.
Keywords: E24; E32; J21; J45; J60; 330; job-separation rate; job-finding rate; worker gross flows; public sector; public-sector employment